Do the most skillful managers herd?. (10th April 2017) - ALDA, MERCEDES
Abstract: This paper analyzes whether herding and skillful managers may coexist. When herding appears, managers tend to present poor timing abilities; however, a weak herding level (a result commonly found in pension funds) may evidence a mixed scenario, where some managers develop skills, and others follow the herd. Additionally, when informational cascades emerge, some managers may act as leaders, anticipating others' movements. Nonetheless, this anticipatory skill does not mean that leaders also anticipate market movements and present timing skills. Our results show herding and inter-temporal herding in a sample of Spanish pension funds, though the imitation behavior is not strong. We also find evidence of a mixed scenario, in which some non-herding managers present timing skills, while herding funds are not able to develop these abilities. Finally, we find successful timing for certain leaders, showing that the anticipation of others' movements does not show real timing abilities.